Creating a Home Elsewhere: Diasporic Imagination in Lee Isaac Chung’s Minari - Fauziyah, Alifya Aini; Manggong, Lestari; Maulana, Sandya (Journal of Language and Literature, 2024)
Minari, a film screened in 2020 directed by Lee Isaac Chung, presents a Korean immigrant family having moved to Arkansas in fulfilling their American dream at the cost of being displaced and out of place. By focusing on the attempt made by Jacob, the father, to recreate the imagined home which refers to South Korea, this study aims to show how the displacement and unhomeliness in the construction of diasporic imagination are displayed in the film. David, the son, not only feels out of place but is also obligated to feel a kind of belonging to both cultures. Jacob’s mother-in-law, Soon-Ja, having newly arrived in the US brings recent memories of home into the family that represent the Korean immigrant perspective of living in the US for the first time. This approach will show how the American film attempts to incorporate the new forms of portraying the ‘elsewhere’ which is an important characteristic of American dream narratives. The analysis is conducted by referring to Bhabha’s unhomeliness and Walder’s displacement in comprehending the contrast between the stereotypical characteristics of Korean immigrants and the American dream through the dialogues and scenes. We would like to argue that Minari follows the convention of the American dream narratives. However, due to displacement and unhomeliness, the film shows how Korean immigrants experience being awkwardly immersed within the mainstream American cultural discourse.